2018
DOI: 10.1136/bmjopen-2017-018523
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with insufficient awareness of breast cancer among women in Northern and Eastern China: a case–control study

Abstract: ObjectivesTo investigate the awareness and knowledge level of breast cancer among Chinese participants.DesignCase–control study.SettingsThis study was based on the database of the minister-affiliated hospital key project of the Ministry of Health of the People’s Republic of China that included 21 Chinese hospitals between April 2012 and April 2013.ParticipantsMatched study was designed among 2978 participants with Han ethnicity aged between 25 and 70.Primary and secondary outcome measuresStudent’s t-test, Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 37 publications
5
25
0
Order By: Relevance
“…Although about three-fourths of participants knew that feeling lumps in the breast and breast enlargement or a change in breast shape were signs of breast cancer, the proportion of participants recognizing other signs or symptoms for breast cancer was low (overall, less than 40%). Findings from other studies, especially from other low–middle income countries, showed similar results [13,28,29,30]. Compared to results from developed countries, the percentage of women in those studies who were aware of breast cancer symptoms was higher, to a certain extent, which can be explained by their greater consciousness of health and higher living standards [29,31].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although about three-fourths of participants knew that feeling lumps in the breast and breast enlargement or a change in breast shape were signs of breast cancer, the proportion of participants recognizing other signs or symptoms for breast cancer was low (overall, less than 40%). Findings from other studies, especially from other low–middle income countries, showed similar results [13,28,29,30]. Compared to results from developed countries, the percentage of women in those studies who were aware of breast cancer symptoms was higher, to a certain extent, which can be explained by their greater consciousness of health and higher living standards [29,31].…”
Section: Discussionsupporting
confidence: 57%
“…Often, according to reports from other developing countries, women lacked awareness of the causes, risks, and prevention of cervical cancer [11,12]. Moreover, the majority of patients with breast cancer and cervical cancer are detected too late, and therefore, are often diagnosed at an advanced stage of the disease, partly due to their inadequate understanding of the symptoms [13,14]. In order to reduce morbidity and mortality and to promote early screening and detection, there need to be comprehensive assessments of knowledge and awareness of breast cancer and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the target women in this study resided in an underdeveloped community with limited health resources, even younger women might have lower awareness of BCS for the early detection of breast cancer. Consistently, Liu and colleagues [30] also showed that about three-quarters of young women aged 25–44 years who lived in rural China, where medical access was limited and health screening was not universal, had poor awareness levels of BCS.…”
Section: Discussionmentioning
confidence: 81%
“…If the symptom is incongruent with these factors, this lead to action thus preventing delay in seeking medical help. Women usually regard the clinical manifestation of BC as a non-serious condition or an ordinary ailment if they do not have knowledge on them, these factors should be fulfilled and emphasised among women [33, 34]. Unfortunately in our study public is not aware of non-lump symptoms as the clinical manifestation of BC.…”
Section: Discussionmentioning
confidence: 84%